Administrative leadership styles and their role in achieving administrative creativity in organizations. - Elarbi HARAN; Boulerbah ZERKOT (Social Sciences Journal, 1970)
The progress and prosperity of organizations depends on its human resources with the intellectualskills and creative abilities on the one hand,And to the leaders of distinguished administrators havethe ability to invest these abilities and skills and providing support to the other.This is achieved through the influence of leadership on the behavior of others and from thedevelopment of their creative abilities through dialogue and encouraging them to face thedifficulties they face while carrying out their duties.If leadership is the ability to influence others byinfluencing their behavior and that enable the commander of guiding them the right direction toachieve the agreed objectives in the light of good human relationships between the leader and hisfollowers.And it is required elements: the leader and the group's goals and impact strength andcoordination.And from which they can make the individuals working in the creative organization